Perkiraan Pasokan Daya Sistem Jawa-Madura-Bali Sampai Tahun 2016 Berdasarkan Indeks Lolp Satu Hari Per Tahun - Zein, Hermagasantos (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Not only operation problem in the electric system but also expansion problem of capacity supply to meet demand in the future that must be handled. This expansion must guarantee adequacy condition of supply in order to avoid lack of supply although there is/are one/more unit black out.Â Adequacy (of power) of an electric system is determined by loss of load probability (LOLP) indexes. This indexes has been definite, i.e. national electric company, PT. PLN, use indexes LOLP 1 day/year. This paper will study adequacy supply in the future, until 2016,Â in the Jawa-Madura-Bali (JAMALI) system based on LOLP indexes by PT. PLN. The result of study will be compared with the planning supply of PT. PLN that was reported in RUPTL (global planning of supply) report-book for 2006-2016. The result indicated that the planning supply of PT. PLN until 2016 is 42431 MW or has LOLP tree digit before coma. In this study, the calculation based on LOLP 1 day/year result the added supply as much as 38086 MW until 2016.Key words: Capacity supply, Adequacy and Loss of load probability indexes.